Concomitant Case of Primary Biliary Cirrhosis and Autoimmune Hemolityc Anemia Responding to Corticosteroid and Ursodeoxycholic Acid in Young Woman - Susanto H Kusuma; Fardah Akil; Amelia Rifai; Rini R Bachtiar; Numan AS Daud; AM Luthfi Parewangi (The Indonesian Society for Digestive Endoscopy, 2016)
Primary biliary cirrhosis (PBC) is an autoimmune liver disease of unknown etiology and is characterized by chronic progressive cholestasis with destruction of the small intrahepatic bile ducts and associated most commonly with antimitochondrial antibodies. PBC is most common in women and is often associated with other autoimmune disease such as autoimmune hemolityc anemia (AIHA), rheumatoid arthritis, thyroiditis, and systemic lupus eritomatosus. We report one case, a 20 years old woman with AIHA have been treated by corticosteroid since last year and she came to the outpatient department (OPD) with fatique and jaundice. The result of laboratory were haemoglobin 8.7 mg/dL, white blood cell 8700 mg/dL, coomb test +2, total bilirubin 33.2 mg/dL, direct bilirubin 29.3 mg/dL, γGT: 297 mg/dL and alkalyphospatase: 158 mg/dL. The result of Abdominal CT scan showed the size of liver and spleen increased and normal common bile duct (CBD). The result of ANA test, anti-nuclear (ANA) and antimitochondrial M2 (AMA M2) antibodies were positive. From the physical examination, laboratory and CT scan Abdomen; the diagnose of this patient was AIHA with PBC. After treatment with corticosteroid (prednison 1mg/kg/day) and ursodeoxicholic acid (UDCA) for several weeks, the clinical manifestation of PBC such as jaundice getting better (the laboratory result: total bilirubin 2.7 mg/dL, direct bilirubin 1.5 mg/dL, gamma GT 80 mg/dL).